2022
DOI: 10.1016/j.jcjp.2022.100038
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared spectroscopic assessment of engineered cartilage for implantation in a pre-clinical model

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Thus, wavelength importance analysis for Classifier 1 showed that the spectral regions responsible for the classification of normal and OA tissue are consistent with absorption regions related to cartilage collagen content (1200–1400 nm) [ 1 , 31 ]. Kendal et al [ 14 , 20 ] have shown that an increasing baseline offset of Vis-NIR spectra reflects matrix maturation in engineered tissue construct. Since significant scattering has been shown in the visible region [ 17 ], the baseline offset in the region (400–600 nm) may reflect a difference in collagen organization between normal and degenerated tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, wavelength importance analysis for Classifier 1 showed that the spectral regions responsible for the classification of normal and OA tissue are consistent with absorption regions related to cartilage collagen content (1200–1400 nm) [ 1 , 31 ]. Kendal et al [ 14 , 20 ] have shown that an increasing baseline offset of Vis-NIR spectra reflects matrix maturation in engineered tissue construct. Since significant scattering has been shown in the visible region [ 17 ], the baseline offset in the region (400–600 nm) may reflect a difference in collagen organization between normal and degenerated tissue.…”
Section: Discussionmentioning
confidence: 99%